1837 Md. Laws 1837 - (:unkn) unknown (My University, 1837)
Ch. 101, An Act for the Preservation of Wild Fowl in the Waters of Smith's Island and its Vicinity, in Somerset County, §§ 1-2: Prohibited shooting fowl from on board an open skiff, canoe, or open boat with any offensive weapon, gun, musket, fowling piece, or pistol in the region know as Hearn's Straits in Somerset County, within fifty yards of any blind for shooting fowl. Violators subject to ten dollar fine.
Keywords: HUNTING REGULATION